Beautiful victim: Romy Schneider in French Occupation cinema. Issue 2 (3rd April 2021) - Hallet, Marion
ABSTRACT: This article analyses Romy Schneider's roles and performances in films depicting the rise of European totalitarianisms and the German Occupation of France during World War II. This small but significant corpus holds an important place in Schneider's career in France as it was decisive in the shaping of her persona (i.e. a media construction) in the 1970s, capitalising on her own personal life and identity being split between Berlin and Paris. Her roles and performances in those films built an atemporal image of Schneider, whose photogeny, eroticisation and Germanness were (and still are) equated with vulnerability and tragedy.